Saturday

October 25, 2014

October 25, 2014

Posted by **billy** on Sunday, November 2, 2008 at 4:31pm.

- math -
**Kelli**, Sunday, November 2, 2008 at 4:39pmSubsitute the 2 for the t, and then the -10, then the 6.9 so you get:

g(2) = 4(2) + 1 = 9

g(-10) = 4(-10) + 1 = -39

g(6.9) = 4(6.9) + 1 = 28.6

:D

- math -
**billy**, Sunday, November 2, 2008 at 4:47pmthanks so much

- math -

**Answer this Question**

**Related Questions**

math - the volume of a rectangular solid is given by expressions given below.in...

math - the volume of a rectangular solid is given by expressions given below.in...

math - x+a=b/3x x= ? i understand that u bring the x to one side but the answer ...

Polynomial Function - Could you help me with the following problem, I dont ...

math - . Given the following function, f(x)=-x^2 -8x find: (a) vertex, (b) axis...

Math - Find the Zeros of the following functions f(x) = x/3 +5 ^ That one is ...

Math - use the given zero to find all the zeros of the function. f(x) = x^3 + x...

Algebra - That is not what the ? is asking. The ? is asking about how to get the...

math - #Algebra 2 Help Please?! If f = (1, 2), (2, 3), (3, 4), (4, 5), g = (1, -...

Algebra - Can you please help me with the following problems? Find the ...